ANALISIS KINERJA GURU SMA N 1 GUNUNG TOAR KECAMATAN GUNUNG TOAR KABUPATEN KUANTAN SINGINGI - Oktariani, Rina; Srikartikowati, Srikartikowati; Armas, Riadi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research is conducted in SMA N 1 Gunung Toar Kuantan Singingi Regency. This research aimed to find out teachers’ performance in SMA N 1 Gunung Toar Kuantan Singingi Regency. Data is collected from 39 teachers at SMA N 1 Gunung Toar Kecamatan Gunung Toar Kabupaten Kuantan Singingi who has dedicated their carrier as theacher for more 2 year. The technique of collecting data used is questionnaire. The technique of analyzing data used is qualitative descriptive method that is changed to be quantitative, thus it uses statistical analysis technique.  The criteria of teachers’ performance in SMA N 1 Gunung Toar Kuantan Singingi Regency are categorized as good, average, and poor.The result of research described that teachers’ performance in SMA N 1 Gunung Toar Kuantan Singingi Regency was categorized as good. It can be seen from the ability of teachers that have done three aspects of performance: score of learning planning process was 83,15%, learning process was 87,25%, and learning evaluation was 79,27%. Key words : learning planning process, learning process, learning evaluation